Hygienic technological innovation of shrimp paste processing for home industry in Pulau Kampai Village, Langkat District - Astrid Fauzia Dewinta, (Journal of Saintech Transfer, 2025)
The catch of rebon shrimp which are abundant in season in the coastal of Pangkalan Susu subdistrict, is utilized by the community of Pulau Kampai village to be processed into shrimp paste which has been passed down for generations and has become a legendary product of this village. One community group that produces shrimp paste is the Atha Baroe home industry. Production yields, which are still on average 50 kg per month, are still very small because this business is still carried out in the traditional way and still requires a touch of technology to improve quality and selling power so that it can compete in the local market. To overcome these problems, the Community Service Team at the Faculty of Agriculture, Universitas Sumatera Utara offers the application of technology in the form of drying machines and vacuum packaging machines. The approach method used in the application of technological innovation is through a participatory, conceptual, theoretical, and practical approach as well as a reflective approach. The application of a drying machine can replace an open drying process that relies on sunlight, to improve the quality and hygiene of the final product through sensory tests which previously obtained e value of 6.550 ≤µ≤ 7.716 to 7.526 ≤µ≤ 8.803, besides that the operating capital of the machine is still affordable. Meanwhile, vacuum packaging machines are not only able to improve quality and maintain product durability but also increase product selling power.